Candida tropicalis arthritis of the knee in a child on chemotherapy treated with intra-articular amphotericin B - Xin Yang Tan; Natalie Woon-Hui Tan; Rina Yue Ling Ong; Michaela Su-Fern Seng; Kenneth Pak Leung Wong (Journal of Orthopaedic Reports)
Fungal osteoarticular infections are rare but severe life-threatening infections, commonly in patients with risk factors such as in the setting of immunosuppression, indwelling prosthesis or intravenous substance abuse. Marked improvement in diagnostic techniques have also contributed to their early detection. Candida species remains the most common cause of fungal osteoarticular infections. While systemic antifungal therapy and surgical drainage remain the mainstay of therapy, intra-articular instillation of antifungals may present a useful adjunct therapy to achieve articular antifungal concentrations. Herein we report a case of a 9-year-old male child with a case of Candida tropicalis septic arthritis of the knee, and our subsequent treatment regimen. This paper also aims to summarise the available evidence surrounding the use of intra-articular instillation of antifungals as adjunct for the treatment of fungal arthritis and highlights the need to further evaluate and develop a standardised treatment regimen.